Pengaruh Pengembangan Karir, Gaya Kepemimpinan Transformasional, Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Surgika Alkesindo Jakarta Pusat - Amoi Sanyo Simanjuntak; Mardi Siswoyo; Khairul Anwar; Marisi Pakpahan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of career development, transformational leadership style, and job satisfaction on employee performance at PT. Surgika Alkesindo, Central Jakarta. The research method used is a quantitative approach with a survey technique through the distribution of questionnaires to 73 respondents. The data were analyzed using multiple regression analysis. The results show that both partially and simultaneously, career development, transformational leadership style, and job satisfaction have a positive and significant effect on employee performance. These findings reinforce the importance of human resource management in designing career development strategies, applying inspirational leadership, and enhancing job satisfaction to achieve optimal productivity and work effectiveness within the company.